Przepisy pozakodeksowe tak zwanej ustawy antyszpiegowskiej z 17 sierpnia 2023 roku - Hoc, Stanisław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article concerns non-code provisions that were adopted on the occasion of the amendment of the Penal Code, related primarily to the new wording of Article 130 of the Penal Code regarding the crime of espionage.
Keywords: espionage; foreign intelligence; crown spy